The Effect of ESG Performance, Tax Avoidance, and Good Corporate Governance on Earnings Management Practices in Mining Companies in Indonesia for the 2020-2024 Period - Nindia Putri Septiani; Wiwin Aminah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study investigates the influence of Environmental, Social, and Governance (ESG) performance, Tax Avoidance, and Good Corporate Governance (GCG) on earnings management among mining sector companies listed on the IDX during 2020–2024. Grounded in Agency Theory (Jensen et al., 1976), the study hypothesizes that ESG performance and GCG negatively influence earnings management, while Tax Avoidance exerts a positive influence. We used secondary data from sustainability reports and yearly reports to create a quantitative descriptive-causal approach. We obtained 75 firm-year observations and 15 enterprises through purposeful sampling. We used the IDX ESG Reporting Index (Form E020) to score ESG performance, the Effective Tax Rate (ETR) to proxy tax avoidance, and the proportion of independent commissioners, managerial ownership, and institutional ownership to measure GCG. Discretionary accruals via the Modified Jones Model were used to measure earnings management. We used EViews 12 to run panel data regression using simultaneous F-tests and partial t-tests. The results reveal that earnings management is strongly and adversely affected by ESG performance and GCG, but has no discernible effect from Tax Avoidance. Theoretically, these results add to the earnings management literature, and practically, they provide regulators and investors with information they can use to evaluate the profitability of mining companies that are adopting sustainability practices.